2021
DOI: 10.1021/acs.jpcc.0c11635
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Charge Storage in Diketopyrrolopyrrole-Based Redox-Active Conjugated Polymers

Abstract: Redox-active conjugated polymers are an emerging class of organic charge storage materials for lithium-ion batteries. The electron conducting conjugated backbone linking the localized redox moieties enables fast electron transfer kinetics. Polymers with redox moieties that have fast redox kinetics and high redox potentials with respect to Li + /Li while being stable under electrochemical environments are ideal for energy storage applications. In this work, we propose diketopyrrolopyrrole (DPP) as a suitable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…For a couple of decades, organic semiconductors (OS) have been extensively investigated as candidate materials for optoelectronic devices such as field-effect transistors (OFETs) [1][2][3][4] , light-emitting devices (OLEDs) [5][6][7][8][9][10] , photovoltaics (OPVs) [11][12][13][14][15][16][17] and more recently for solar-fuel production [18][19][20][21][22][23] and energy storage such as Lithium-ion batteries (LIB). [24][25][26][27][28][29] OS are very appealing thanks to several intrinsic characteristics of organic materials viz. processability from solution, mechanical flexibility enabling integration to curved or flexible substrates, easy functionalization leading to the possibility to fine-tune their optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…For a couple of decades, organic semiconductors (OS) have been extensively investigated as candidate materials for optoelectronic devices such as field-effect transistors (OFETs) [1][2][3][4] , light-emitting devices (OLEDs) [5][6][7][8][9][10] , photovoltaics (OPVs) [11][12][13][14][15][16][17] and more recently for solar-fuel production [18][19][20][21][22][23] and energy storage such as Lithium-ion batteries (LIB). [24][25][26][27][28][29] OS are very appealing thanks to several intrinsic characteristics of organic materials viz. processability from solution, mechanical flexibility enabling integration to curved or flexible substrates, easy functionalization leading to the possibility to fine-tune their optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…McCulloch et al have recently reported three donor-acceptor (D-A) type glycolated TDPPs and highlighted the relationship between the polaron delocalization and the OECT mobility. One of these DPP polymers had a high mC* of about 300 F cm À1 V À1 s À1 but a high threshold voltage of 0.52 V. [37][38][39][40][41] Thienylenevinylene (TVT) and thiophene-benzothiadiazole-thiophene (TBTT) are two popular electron-donating units used to form D-A type polymers with high charge-carrier mobilities in OFETs. [42][43][44] Incorporating the highly p-extended TVT and TBTT units in the main chain with DPP promotes intermolecular p-p stacking.…”
Section: Introductionmentioning
confidence: 99%
“…Samuel et al 117 developed two donor-acceptor polymers, each with a conjugated backbone made up of repeating units containing diketopyrrolopyrrole (DPP) and thiophene (T) groups. The Li anode and 1 M LiClO 4 in 1 : 1 (v/v) DOL/DME as the electrolyte were applied in this work.…”
Section: Li-ion Batteriesmentioning
confidence: 99%